HUBUNGAN POLA MAKAN DENGAN PENURUNAN FUNGSI GINJAL PADA PASIEN DM TIPE 2 RAWAT JALAN DI RSUP DR.SARDJITO YOGYAKARTA - , ANNAAFI ANNUUR UTORO, Susetyowati, DCN., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Based on the most disease pattern of internal medicine outpatients at Dr. Sardjito Central General Hospital, DM disease was occupied in the first ranks. Basically, DM disease could not be cured, but it could be controlled in term of reducing the effect of complications. One of the methods to reduce the effect of complications is by planning the proper dietary pattern. Some studies revealed the poor in planning the dietary pattern such as the high intake of fat, saturated fat, sodium and carbonated beverages, which might cause decline in kidney function. Objective : To determine the relationship of dietary pattern, the intake of energy, protein, fat, carbohydrates, and the consumption of soft drinks with decline in kidney functions in type 2 diabetes mellitus outpatients in Dr. Sardjito Yogyakarta. Method : This observational study using cross-sectional design. The research was conducted with the primary data (data of patientâs characteristics, anthropometry, 24-hours of food recallâs data for two consecutive days in dissuccession and food frequencyâs data) and secondary data (laboratory test results by using the level of creatinine). The patient's dietary pattern such as the intake of energy, protein, fats, and carbohydrates as well as the consumption of soft drinks is obtained from the results of 24-hours food recall and food frequency (FFQ). The decline in kidney functionâs data is obtained using the MDRD formula that requires the data of age, sex, race, and serum creatinine levels. The analysis tests were used to determine the relationship between dietary pattern (intake of energy, protein, fat and soft drinks) and decline in kidney function are Chi-square test, Somersâd test and logistic regression. Results : There is a relationship between intake of energy, protein, and carbohydrate with decline in kidney function (p < 0,05). However, there is no relationship between intake of fat and soda consumption with decline in kidney function (p > 0,05). There is a relationship between age and decline in kidney function (p = 0,021) and duration of diabetes disease and decline in kidney function (p = 0,040). Last, there is no relationship between obesity and decline in kidney function (p > 0,05). Conclusion : There is a significant relationship between intake of energy, protein and carbohydrate with decline in kidney function in the type 2 of diabetesâ outpatients in Dr. Sardjito Yogyakarta.